Influence of aluminum microparticles on plasma chemistry and structural dynamics of ns-laser ablated 5-methyl-1H-tetrazole in argon atmosphere. Issue 10 (21st September 2022) - Deng, K.; Li, S. W.; Zhao, Y. L.; Shi, J. C.; Luo, S. N.
Abstract : Aluminum microparticles as an additive in ns-laser ablation of C2 H4 N4, can enhance the emission intensity of C2 and CN, and promote the plasma expansion. Abstract : The effects of Al microparticles on plasma chemistry and structural dynamics of laser-ablated pure and aluminized 5-methyl-1 H -tetrazole (C2 H4 N4 ) are investigated with nanosecond laser induced breakdown spectroscopy (LIBS). Time-resolved and time-integrated emission spectra of the CN violet system (B 2 Σ + − X 2 Σ +, Δ ν = 0 sequence) and C2 swan system (d 3 Πg − a 3 Πu, Δ ν = 0 sequence) are obtained and analyzed. The intensities of the CN and C2 emissions are increased by the Al microparticles, and their lifetimes in the laser-induced plasma are also altered. Furthermore, spatially and temporally resolved imaging measurements of the CN and C2 emissions are also conducted. The addition of Al microparticles leads to facilitated expansion and splitting of the laser-induced plasma.